2014
DOI: 10.1186/1477-7819-12-152
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy without prophylactic central neck dissection in clinically node-negative papillary thyroid cancer: is it an adequate treatment?

Abstract: BackgroundCervical lymph node metastases in papillary thyroid cancer are common. Although central neck dissection is indicated in clinically nodal-positive disease, it remains controversial in patients with no clinical evidence of nodal metastasis. The aim of this retrospective study was to determine the outcomes of clinically lymph node-negative patients with papillary thyroid cancer who underwent total thyroidectomy without a central neck dissection, in order to determine the rates of recurrence and reoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 38 publications
1
46
0
2
Order By: Relevance
“…Thyroidectomy and therapeutic neck dissection is recommended for patients with known metastatic lymph nodes identified either pre-or intraoperatively (3). However, the benefit of prophylactic central lymph node dissection (CLND) in patients who have no pre-or intraoperative evidence of nodal metastasis remains controversial (3,5,6). Some argue that CLND may reduce the recurrence rate of lymph node metastasis, while others claim that patients receive no benefit, yet experience increased risk of permanent hypoparathyroidism and recurrent laryngeal nerve injury (6)(7)(8).…”
Section: V600ementioning
confidence: 99%
“…Thyroidectomy and therapeutic neck dissection is recommended for patients with known metastatic lymph nodes identified either pre-or intraoperatively (3). However, the benefit of prophylactic central lymph node dissection (CLND) in patients who have no pre-or intraoperative evidence of nodal metastasis remains controversial (3,5,6). Some argue that CLND may reduce the recurrence rate of lymph node metastasis, while others claim that patients receive no benefit, yet experience increased risk of permanent hypoparathyroidism and recurrent laryngeal nerve injury (6)(7)(8).…”
Section: V600ementioning
confidence: 99%
“…The reasons why such small percentage of FNAC performed is in part due to the fact that only a few endocrinologists perform FNAC but also because a lot of patients refuse it. While there is general acceptance that clinically evident nodal disease should be removed for therapeutic purposes, there is strong debate among endocrine surgeons regarding PCND (3,6,9,12,21,22). According to its proponents, PCND lowers the risk of local recurrence and increases long-term survival without increasing the risk of permanent morbidity (23).…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic value of lymph node metastases in PTC is a matter of debate. If some authors have shown that lymph node metastases do not decrease survival rate [5][6][7][8][9][10], others have suggested that lymph node involvement is a significant prognostic factor affecting both disease-free [11] and overall survival [12,13] rate. Consequently, also the optimal extent of cervical lymphectomy remains controversial.…”
Section: Discussionmentioning
confidence: 99%